Study on the preparation process of quinoa anti-hypertensive peptide and its stability - Fan, Xing; Ma, Xuemei; Maimaitiyiming, Ruxianguli; Aihaiti, Aihemaitijiang; Yang, Jiangyong; Li, Xianai; Wang, Xiaoyun; Pang, Guangxian; Liu, Xiaolu; Qiu, Chenggong; Abra, Redili; Wang, Liang (Frontiers in Nutrition, 2023)
Quinoa seeds are a food resource rich in protein, vitamins, minerals, and other functional components such as polyphenols, polysaccharides, and saponins. The seeds have become favored by modern consumers due to being gluten-free and featuring a high protein content. This study focused on the preparation of quinoa peptides by short-time enzymatic-assisted fermentation. Quinoa flour (QF) was mixed with water in a certain ratio before being enzymatically digested with 0.5% amylase and 0.1% lipase for 6 h. Then, 16 bacterial taxa were used for fermentation, respectively. The peptide content in the resulting fermentation broths were determined by the biuret method. The dominant taxon was then identified and the peptide content, amino acid distribution, and molecular weight distribution of the prepared quinoa peptides were analyzed. Further, the temperature, pH, metal ions, organic solvents, ion concentration, and anti-enzyme stability of the quinoa anti-hypertensive peptides of different molecular weights after fermentation with the dominant taxon were investigated. Finally, the inhibitory activity of fermented quinoa peptides on bacteria was studied.The results show that the peptide content of the fermentation broth reached 58.72±1.3% at 40 h of fermentation with Lactobacillus paracasei and the molecular weights of the hydrolyzed quinoa peptides were mainly distributed below 2 kDa by polyacrylamide gel. The ACE inhibition and peptide retention of the 0-3 kDa quinoa peptides were screened to be high and stable. At the same time, the inhibitory activity of quinoa peptide after fermentation on E. coli was obvious. This study provides a theoretical basis for further research on quinoa peptides and applications for their industrial production.